Analyzing the Thermodynamic Phase Partitioning of Mixed Phase Clouds Over the Southern Ocean Using Passive Satellite Observations - Coopman, Q.; Hoose, C.; Stengel, M. (John Wiley and Sons, 2021)
The thermodynamic phase transition of clouds is still not well understood, therefore, the partitioning of ice and liquid in mixed phase clouds is often misrepresented in numerical models. We use 12 years of cloud observations from the geostationary Spinning Enhanced Visible and InfraRed Imager over the Southern Ocean to detect clouds which contain both liquid and ice pixels at their tops and we retrieve microphysical and radiative properties in each cloud object. The results show that large cloud droplet effective radius coincides with high ice fraction and high ice optical thickness for cloud top temperatures higher than −8 °C. We also found that the density of ice pixel clusters increases with the cloud ice fraction, for ice fraction lower than 0.5, suggesting a multiplication of ice pockets in line with previous studies, particularly efficient for clouds with high perimeter fractal dimension. Plain Language Summary Clouds with coexisting liquid droplets and ice crystals are frequent but they are still not well understood and often misrepresented in numerical models. We analyze the temperature, the optical properties of clouds, and the size of droplets and ice crystals from 12 years of satellite observations over the Southern Ocean. We find that clouds with large droplets are more likely to undergo glaciation than clouds with small droplets and that at temperatures higher than −8 °C the glaciation is probably associated with a higher concentration of ice crystals. We also analyze how liquid and ice are spatially distributed within clouds and we highlight that multiple ice pockets are formed when clouds glaciate rather than spreading from one ice pocket to the entire cloud. A better understanding of clouds allows a better representation of their interaction with the environment and therefore their impact on the climate. Clouds precipitate more easily if they consist of ice crystals, potentially reducing the lifetime of clouds and impacting the radiation balance at the surface and top of the atmosphere. Also, ...